Producer Strategy in Distribution of Yogyakarta Special Fund Documentary Film “YK48” - Basri, Azzahra Silvia; Arifianto, Budi Dwi (Jogjakarta Communication Conference (JCC), 2025)
Documentary films face challenges in distribution, especially in reaching a wider audience. This study analyzes the distribution strategy of the documentary film "YK48," funded by the Yogyakarta Special Fund (Danais) by Pehagengsi. Using a qualitative approach with a case study method, data was collected through in-depth interviews, observations, and document studies. The study results show that the distribution strategy of "YK48" focuses on community screenings as the main channel, supported by film festivals, social media, and collaboration with alternative screening spaces. This community-based approach allows the film to reach more audiences even though it does not prioritize distribution in cinemas or digital platforms. The film won an award at the 2023 Tanah Lado Film Fest and received a recommendation from the Indonesian Film Festival (FFI). This study confirms that a community-based distribution strategy can be an effective model for independent filmmakers to expand the reach of documentary films in Indonesia.